PENGARUH PENERAPAN MODEL SSCS TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK PADA PEMBELAJARAN IPA KELAS VIII - Hasibuan, David; Tandililing, Edy; Arsyid, Syaiful B (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2023)
This research aims to determine the influence of application the Search Solve Create Share (SSCS) on the learning activities of students in 8th grade science learning. Based on the effect of learning activities that are very influential on the brain's capture and recall power, it is appropriate to use a special learning model. In this case, the SSCS model was tried for later use in improving student learning activities. This research was conducted in SMP Negeri 2 Pontianak on odd semester 2018-2019. The form of this study used pre-experimental designs with the design of intact-group comparison. The research sample consisted of 30 students of class VIII A as the experimental class and 25 students of class VIII B as the control class. Research data collection uses observation techniques with observation sheet learning activity instruments. The results of the data analysis showed that there were significant differences between the learning activities of students in the experimental class and the control class with the Mann-Whitney test value assisted by SPSS 22 for Windows application 0.000 <0.05 (5%). It can be concluded that there is a significant influence of the application the SSCS model on the learning activities of students in the VIII grade science learning in Pontianak Public Middle School 2.